If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + -1) + -4(x + -4) = -5 Reorder the terms: 3(-1 + 5x) + -4(x + -4) = -5 (-1 * 3 + 5x * 3) + -4(x + -4) = -5 (-3 + 15x) + -4(x + -4) = -5 Reorder the terms: -3 + 15x + -4(-4 + x) = -5 -3 + 15x + (-4 * -4 + x * -4) = -5 -3 + 15x + (16 + -4x) = -5 Reorder the terms: -3 + 16 + 15x + -4x = -5 Combine like terms: -3 + 16 = 13 13 + 15x + -4x = -5 Combine like terms: 15x + -4x = 11x 13 + 11x = -5 Solving 13 + 11x = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 11x = -5 + -13 Combine like terms: 13 + -13 = 0 0 + 11x = -5 + -13 11x = -5 + -13 Combine like terms: -5 + -13 = -18 11x = -18 Divide each side by '11'. x = -1.636363636 Simplifying x = -1.636363636
| .25(8+4x)-.5(8+2x)= | | 3x+X/5 | | 5/2x=2/3 | | (3y+9)(3y-9)= | | (2x+5t)(s-4t)= | | (8x-2)(x-5)= | | x*x-20x+36=0 | | 3(110)=6-9z | | 0.5x+.25y=36 | | 3(-19)=6-9z | | 3/n-40+2n=15 | | (1-1)(1-2)= | | 4a+3ab=7 | | 3(2.2)=6-9z | | 20x+35y=150 | | 7-22-1=9 | | (2x+7)x(x+6)= | | 3(-1)=6-9z | | a^2+n+2b^2= | | x^6+7x-8=0 | | 3a^2(ab^2+b^2)= | | -2x-3x+8=0 | | 3(0)=6-9z | | 0=y+(x/4)-4 | | 3m2=10 | | 7a+12ab-(2a-b)+3b | | 0=n+x-2 | | 4x^3+4x^2=10 | | 3x-8x+7 | | 218=11x+75 | | 3w=6-9(0) | | -46+4x=14 |